Reactivation of SOX17 program as immune-evasion mechanism in early colorectal cancer Development - Ahadova, Aysel; Kloor, Matthias (The New England journal of medicine, 2024)
A recent study suggests that reexpression of a protein found during fetal development plays a role in the suppression of immunity in early colorectal adenomas and cancers.